Mechanical Properties and Stretch Forming Behaviour of Electron Beam Welded Titanium Sheets of Grade-2 and Grade-5. (2017) - Lin Prakash, P.S.; Rajak, Bijoy; Panda, Sushanta Kumar; Roy, Gour Gopal; Jha, Maha Nand; Mascarenhas, Martin
Abstract: Titanium sheet metal components have wide applications in aerospace and nuclear industries, and the weight of these components can be reduced by applications of tailor welded blanks. In present study, titanium Grade-2 and Grade-5 sheets were electron beam welded successfully at a speed of using beam current and accelerating voltage of and . The microhardness and microstructure of the weld zone were characterized, and subsequently the stretch forming behaviour was studied by uni-axial tensile and Erichsen cupping tests. There was significant decrease in Erichsen cup height with failure across the harder weld zone unlike uni-axial tensile deformation mode.